Mesorhizobium huakuii HtpG Interaction with nsLTP AsE246 Is Required for Symbiotic Nitrogen Fixation. Issue 1 (14th February 2019) - Zhou, Donglai; Li, Yanan; Wang, Xuting; Xie, Fuli; Chen, Dasong; Ma, Binguang; Li, Youguo
Abstract : The Mesorhizobium huakuii molecular chaperone HtpG interacts with the lipid transfer protein AsE246, which plays an essential role in effective root nodule development and symbiotic nitrogen fixation. Abstract: Plant nonspecific lipid transfer proteins (nsLTPs) are involved in a number of biological processes including root nodule symbiosis. However, the role of nsLTPs in legume-rhizobium symbiosis remains poorly understood, and no rhizobia proteins that interact with nsLTPs have been reported to date. In this study, we used a bacteria two-hybrid system and identified the high temperature protein G (HtpG) from Mesorhizobium huakuii that interacts with the nsLTP AsE246. The interaction between HtpG and AsE246 was confirmed by far-Western blotting and bimolecular fluorescence complementation. Our results indicated that the heat shock protein 90 (HSP90) domain of HtpG mediates the HtpG-AsE246 interaction. Immunofluorescence assay showed that HtpG was colocalized with AsE246 in infected nodule cells and symbiosome membranes. Expression of the htpG gene was relatively higher in young nodules and was highly expressed in the infection zones. Further investigation showed that htpG expression affects lipid abundance and profiles in root nodules and plays an essential role in nodule development and nitrogen fixation. Our findings provide further insights into the functional mechanisms behind the transport of symbiosome lipids via nsLTPs in root nodules.